(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This paper presents the signal strength measurement of the 4G network for an outdoor environment. The signal strength is measured at the Universiti Teknologi Malaysia (UTM) at 1.8 GHz and 2.6 GHz. The signal measurement is compared with the simulation using WinProp software. The database was created for the simulation, and the received signals were recorded at certain locations. The measured and simulated results show that the signal is comparable, where the highest signal is -56 dBm at 1.8 GHz and -49 dBm at 2.6 GHz.